2011
DOI: 10.1021/jp205441s
|View full text |Cite
|
Sign up to set email alerts
|

Electronic Structure, Molecular Electrostatic Potentials, Vibrational Spectra in Substituted Calix[n]arenes (n= 4, 5) from Density Functional Theory

Abstract: Electronic structure, molecular electrostatic potential, and vibrational frequencies of para-substituted calix[n]arene CX[n]-R (n = 4, 5; R = H, NH(2), t-Bu, CH(2)Cl, SO(3)H, NO(2)) and their thia analogs (S-CX[n]-R; with R = H and t-Bu) in which sulfur bridges two aromatic rings of CX[n] have been derived from the density functional theory. A rotation around CH(2) groups connecting the phenol rings engenders four, namely, cone, partial cone, 1,2-alternate, and 1,3-alternate CX[n]-R conformers. Of these, the c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
10
0
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 83 publications
(126 reference statements)
0
10
0
1
Order By: Relevance
“…Electrostatic potential (ESP) surfaces of the absorbates molecules and ESP surfaces of the POSS cages are shown in the ESI. † Natural bond orbital (NBO) analysis [45][46][47] was performed and the charges for the molecules are provided in ESI † (Table S3). All diatomic molecule atoms are negatively charged when they are at the center of T 10 indicating that the T 10 donates electron density to the absorbates; this is with the exception of the carbon of CO, where the oxygen is more electronegative than the carbon.…”
Section: Pccp Papermentioning
confidence: 99%
“…Electrostatic potential (ESP) surfaces of the absorbates molecules and ESP surfaces of the POSS cages are shown in the ESI. † Natural bond orbital (NBO) analysis [45][46][47] was performed and the charges for the molecules are provided in ESI † (Table S3). All diatomic molecule atoms are negatively charged when they are at the center of T 10 indicating that the T 10 donates electron density to the absorbates; this is with the exception of the carbon of CO, where the oxygen is more electronegative than the carbon.…”
Section: Pccp Papermentioning
confidence: 99%
“…56 The topography of the scalar field such as molecular electrostatic potential (MESP) has been utilized to estimate the size and shape of calixarene derivatives. 57 Moreover, the cooperativity effects accompanying the underlying molecular interactions can be brought about through MESP. 58 To understand the driving force responsible for encapsulation of small gaseous molecules within calix [4]arene, molecular dynamics simulations were carried out by Deakyne et al 59 Despite the aforementioned studies, almost no endeavor, within DFT, appears to have been made toward the description of partial thia-substituted calix [4]arenes.…”
Section: ■ Introductionmentioning
confidence: 99%
“…The calix [4]arene (C4A) has four conformers [25,[29][30][31][32]. Previous studies have demonstrated that the cone conformer is the most stable [29,32].…”
Section: Introductionmentioning
confidence: 99%
“…Four intramolecular hydrogen bonds O-H· · · O are formed in the cone conformers of C4A, which allows C4A to act as host for a wide range of guests. Thus, C4A is an excellent model in which to study intramolecular hydrogen bonding in the excited state [32][33][34][35]. However, little information is available on electronic excited-state intramolecular hydrogen bonding due to the extremely short timescales involved.…”
Section: Introductionmentioning
confidence: 99%